Relative Ability and Target Difficulty in Managers’ Decisions to Delegate Tasks - Laksono, Bayu Rama; Hidayat, Rendra Arief; ., Aisyaturrahmi; Kurniawan, Widiar Onny (Journal of Ecohumanism, 2024)
This study aims to examine whether Relative Ability and Target Difficulty affect managers’ decisions in delegating tasks to employees.